Gastroprotective Effects of Dendropthoe pentandra Leaf Ethanol Extract on Peptic Ulcer Animal Models - Fitrya Fitrya; Annisa Amriani; Rennie Puspa Novita; Fadila Kurnia (Science and Technology Indonesia, 2023)
Dendrophthoe pentandra (Loranthaceae) is a semi-parasitic plant with several diverse metabolites and biological activities and is widely used in traditional medicine. This study aims to evaluate the gastroprotective effectiveness of the ethanol extract of D. pentandra leaves in animals induced by an acute peptic ulcer with absolute ethanol. The gastroprotective effect of the extract (100, 250 and 500 mg/kg doses) was evaluated through ulcer index parameters, physicochemical properties of gastric fluid, and histopathological analysis. The study results of the study showed that the ethanol extract of D. pentandra leaves at a dose of 500 mg/kg could provide a protective effect equivalent to omeprazole. Histopathological analysis proved the improvement of the mucous membrane structure in the animals pre-treated with the extract. Based on these findings, it can be concluded that the ethanol extract of D. pentandra leaves is effective as an anti-ulcer drug, so it is feasible to be developed as a gastroprotective from herbal.